ANALYZING THE EFFECTIVENESS OF HUMANITARIAN SUPPLY CHAIN PRACTICES: EVIDENCE FROM NATURAL DISASTER INTERVENTIONS IN INDIA - Rachna Chopra; Jagdeep Singla (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Purpose – This study investigates the effectiveness of humanitarian supply chain practices in India, focusing on how coordination, information sharing, and logistics capability influence disaster relief performance. It addresses the urgent need for empirical validation of inter-organizational practices that enhance responsiveness and resilience during natural disaster interventions. Design/methodology/approach – A quantitative, cross-sectional research design was adopted. Data were collected from 406 stakeholders-including government officials, NGO workers, and logistics providers—across five disaster-prone Indian states using a structured questionnaire. Structural Equation Modeling (SEM) was applied to test relationships among key constructs and validate the conceptual model. Findings – The findings confirm that coordination, information sharing, and logistics capability significantly impact relief performance. Logistics capability emerged as the strongest predictor of performance (β = 0.447), followed by coordination (β = 0.421) and information sharing (β = 0.386). The model demonstrated strong explanatory power (R² = 0.643), with information sharing mediating the effects of coordination and logistics on performance outcomes. The study also revealed interdependencies between strategic and operational components of humanitarian supply chains. Originality/value – This research provides one of the few empirical, multi-stakeholder analyses of humanitarian supply chain effectiveness in India. It bridges the gap between theory and practice by offering data-driven insights relevant to disaster-prone regions. The study highlights the need for coordinated planning, digital integration, and stakeholder capacity-building to strengthen India’s disaster response mechanisms.